A Trait‐based framework for mutation bias as a driver of long‐term evolutionary trends. Issue 5 (27th March 2015) - Xue, Julian Z.; Costopoulos, André; Guichard, Frédéric
Abstract : Previous work has shown that mutation bias can direct evolutionary trends in genotypic space under strong selection and rare mutation. We present an extension of this work to general traits of the organism. We do this by allowing many different genotypes, with different fitnesses, to have the same trait value. This approach makes novel predictions and shows that the outcome of evolution for a trait is influenced by mutation bias as well as the fitness distribution of the genotypes that have the same trait value. This distribution can alter evolution in interesting ways, depending on the likelihood of generating high fitness mutants. We also show that mutation bias can direct evolution when many mutants are present at any one time. We demonstrate that mutation bias can drive long‐term evolutionary trends when the environment is constantly changing. Under biologically realistic conditions, we show that mutation bias can counter strong gradients of environmental selection over time. We conclude that evolutionary trends can be quite independent of the environment, even when they depress population fitness. Finally, we show that entropy can be a powerful source of mutation bias and can drive evolutionary trends. © 2015 Wiley Periodicals, Inc. Complexity 21: 331–345, 2016